CANCELLATION OF OWNERSHIP CERTIFICATE ON THE BASIS OF UNLAWFUL ACT (Decision Study: No. 58/pdt.G/2020/PN. Kwg) - Maulida Ridfar, Lulu; Guntara, Deny; Abas, Muhamad (EKSEKUSI, 2025)
Land plays a strategic role not only as a place to live but also as a source of economic and social status. However, legal issues such as document forgery, duplicate certificates, and land grabbing still frequently occur. This study uses a normative juridical method to examine the cancellation of land certificates due to unlawful acts (PMH) based on Article 53 of the State Administrative Law and Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency No. 11 of 2016. The principle of legal certainty in Article 19 of the UUPA is an important basis for resolving land disputes. The case study of the Karawang District Court Decision No. 58/Pdt.G/2020/PN.Kwg, which was upheld by the Bandung High Court No. 207/PDT/2021/PT.BDG, emphasizes the importance of caution by land officials and the application of the principle of ius curia novit and the social function of land as regulated in Article 6 of the UUPA.